Respuesta :
The simplified form is (x+8)/ (x-6)(x+4).
In order for the expression to be undefined, the denominator must be equal to 0. Therefore you can set (x-6)(x+4)=0 so theerefore x=6 and x=-4
In order for the expression to be undefined, the denominator must be equal to 0. Therefore you can set (x-6)(x+4)=0 so theerefore x=6 and x=-4
Answer:
The correct options are D and F.
Step-by-step explanation:
The given expression is
[tex]\frac{x+8}{x^2-2x-24}[/tex]
The given expression is undefined if the value of denominator is equal to 0.
Equate the denominator value equal to 0.
[tex]x^2-2x-24=0[/tex]
The middle term can be written as -6x+4x.
[tex]x^2-6x+4x-24=0[/tex]
[tex]x(x-6)+4(x-6)=0[/tex]
[tex](x-6)(x+4)=0[/tex]
Equate each factor equal to 0.
[tex]x-6=0\Rightarrow x=6[/tex]
[tex]x+4=0\Rightarrow x=-4[/tex]
Therefore the given expression is undefined at x=6 and x=-4. Options D and F are correct.